Loneliness and its association with psychological and somatic health problems among Czech, Russian and U.S. adolescents - Stickley, Andrew; Koyanagi, Ai; Koposov, Roman; Blatný, Marek; Hrdlička, Michal; Schwab-Stone, Mary; Ruchkin, Vladislav (BMC psychiatry, 2016)
BACKGROUND: Loneliness is common in adolescence and has been linked to various negative outcomes. Until now, however, there has been little cross-country research on this phenomenon. The aim of the present study was to examine which factors are associated with adolescent loneliness in three countries that differ historically and culturally-the Czech Republic, Russia and the United States, and to determine whether adolescent loneliness is associated with poorer psychological and somatic health. METHODS: Data from a school survey, the Social and Health Assessment (SAHA), were used to examine these relations among 2205 Czech, 1995 Russian, and 2050 U.S. male and female adolescents aged 13 to 15 years old. Logistic regression analysis was performed to examine if specific demographic, parenting, personal or school-based factors were linked to feeling lonely and whether lonely adolescents were more likely to report psychological (depression and anxiety) or somatic symptoms (e.g. headaches, pain). RESULTS: Inconsistent parenting, shyness, and peer victimisation were associated with higher odds for loneliness in at least 4 of the 6 country- and sex-wise subgroups (i.e. Czech, Russian, U.S. boys and girls). Parental warmth was a protective factor against feeling lonely among Czech and U.S. girls. Adolescents who were lonely had higher odds for reporting headaches, anxiety and depressive symptoms across all subgroups. Loneliness was associated with other somatic symptoms in at least half of the adolescent subgroups. CONCLUSION: Loneliness is associated with worse adolescent health across countries. The finding that variables from different domains are important for loneliness highlights the necessity of interventions in different settings in order to reduce loneliness and its detrimental effects on adolescent health.
Keywords: Depressive symptoms; Spojené státy americké; Humans; úzkost; chování mladistvých; oběti zločinu; Female; mladý dospělý; vztahy mezi rodiči a dětmi; lidé; Loneliness; United States; Anxiety; Correlates; osamocení; ženské pohlaví; Male; Adolescent Behavior; Adolescent; vyrovnaná skupina; Czech Republic; Parent-Child Relations; Rusko; Young Adult; Peer Group; Russia; Depression; Česká republika; mužské pohlaví; deprese; Crime Victims; Somatic symptoms; mladiství